The Impact of Tik Tok Application on the Lifestyle of STABN Raden Wijaya Wonogiri Students - Rosanti, Devi Metta; Asih, Situ; Sudarto, Sudarto (Institut Agama Islam Negeri (IAIN) Curup, 2024)
The negative impact of using Tik Tok social media is that students lose time which should be used for productive activities and instead are used for laziness, causing students to behave consumptively in online shopping due to the influence of creator content in Tik Tok, as for the case that occurred in the 2019 batch of STABN Raden Wijaya students. Factors that influence student lifestyles include addiction to scrolling Tik Tok so that students are lazy and forget about their obligations, increasing online shopping culture, friendship environment, creator content that is watched when promoting goods. This research uses qualitative research methods, with a descriptive approach, data collection techniques are carried outthrough interviews, observation, and documentation. The results obtained in this study are STABN Raden Wijaya Wonogiri Class of 2019 students who often use Tik Tok social media, the content watched on the algorithm of six out of six students has an impact on student behavior and lifestyle. Tik Tok social media has an impact on (clothing) dressing style (finance) consumptive lifestyle and (leisure)wasting a lot of time using social media